Perceptions of nurses on access to structural empowerment in a hospital in the Western Cape - Gladness Roji; Karien Jooste (AOSIS, 2020)
Background: Structural empowerment is an ever-evolving concept interpreted and applied in many different ways as it focuses on the structures in a healthcare organisation to allow competent nurses to manage empowering opportunities in a professional manner. At a public hospital in the Western Cape, nurses complained about a lack of access to structural empowerment in a hospital, including structures of power, such as clear information, to partake in important decisions. Objectives: The purpose of this study was to describe how nurse managers could support nurses in accessing structural empowerment through power resources. Method: A quantitative design was followed with a survey. The accessible population in this study was different categories of nurses of professional, enrolled and assistant nurses (N = 200), which were on duty at the time of data gathering. The sample was selected by means of probability sampling (n = 110). An existing instrument based on a five-point Likert scale was distributed that took 45 minutes to complete. Descriptive and inferential statistics were calculated, and the chi-square was used to indicate statistical significance differences among the nursing categories on the items (p 0.05). Results: The general results indicated that the majority of nurses had challenges to access structural empowerment through power sources (information, support and resources). Significant differences were found between nurse categories for having the necessary supplies for the job (p = 0.043) and rewards for unusual job performance (p = 0.023). Those aspects on which no significant differences were found are of utmost importance, as they indicate the urgency of addressing limitations in power sources for all categories of nurses. Conclusion: Empowerment can be achieved by enabling access to structural empowerment through power sources (i.e. opportunities, information, resources and support) at different levels for all categories of nurses.